2022
DOI: 10.1002/met.2063
|View full text |Cite
|
Sign up to set email alerts
|

Historical analysis (2001–2019) of low‐level wind shear at the Hong Kong International Airport

Abstract: This paper analyses over 10,000 quality‐controlled pilot reports of low‐level wind shear (‘wind shear’) at the Hong Kong International Airport (HKIA; ICAO code: VHHH) between 2001 and 2019. HKIA is well known for its susceptibility to wind shear, which is a potential hazard for aircraft during landing and take‐off. Wind shear at HKIA exhibits strong seasonality with double peaks in the middle of the spring and summer months. There is a strong diurnal cycle in report numbers, peaking towards the afternoon, as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In recent years, thanks to advancements in monitoring technology and forecasting capabilities, aviation accidents caused by weather-related factors have seen a significant reduction [37]. However, incidents involving aircraft unable to perform normal takeoffs and landings due to wind shear remain alarmingly common [83][84][85][86][87][88], and one significant cause of wind shear is a microburst. Dry microbursts, in particular, are challenging to detect and pose greater dangers.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, thanks to advancements in monitoring technology and forecasting capabilities, aviation accidents caused by weather-related factors have seen a significant reduction [37]. However, incidents involving aircraft unable to perform normal takeoffs and landings due to wind shear remain alarmingly common [83][84][85][86][87][88], and one significant cause of wind shear is a microburst. Dry microbursts, in particular, are challenging to detect and pose greater dangers.…”
Section: Discussionmentioning
confidence: 99%
“…It is among the airports that suffer the most from LLWS on a global scale. Perhaps every 400 to 500 flights, a notable LLWS event will happen (Hon & Chan, 2022). The topographical features of the southern region of HKIA, as depicted in Figure 2, enhance the effects of LLWS, thereby causing disturbances in the air currents throughout the entire glide path.…”
Section: Methodsmentioning
confidence: 99%
“…Innumerable observation-based and simulation studies demonstrated that HKIA's complex land-sea contrast and intricate orography are favorable conditions for the emergence of low-level wind shear [49]. Approximately every 400-500 fights, a signifcant low-level wind shear event takes place [50]. From 1998, when HKIA frst opened, through 2015, 97% of reports indicated level-level wind shear between 15 and 25 knots [51].…”
Section: Study Locationmentioning
confidence: 99%